Burrows with Chimneys of the Fiddler Crab Uca thayeri: Construction, Occurrence, and Function - Gusmao-Junior, Joao B. L.; Machado, Glauco B. O.; Costa, Tânia Marcia [UNESP] (Acad Sinica Inst Zoology, 2012)
Joao B. L. Gusmao-Junior, Glauco B. O. Machado, and Tania M. Costa (2012) Burrows with chimneys of the fiddler crab Uca thayeri: construction, occurrence, and function. Zoological Studies 51(5): 598-605. Building of soil structures is observed in a variety of semi-terrestrial crustaceans. In fiddler crabs (Genus Uca), this behavior occurs in several species, some of which build structures that are largely ornamental and others construct barriers that are apparently for defense. Although there is a relative abundance of studies on this type of behavior in Uca, the relationship between the social context and the occurrence of these structures remains poorly studied. Thus, this study attempted to analyze in detail the construction, occurrence, and function of mud chimneys built by the fiddler crab Uca thayeri; these sedimentary structures are possibly associated with burrow defense. Field investigations and laboratory experiments were conducted. Both sexes were often found in burrows with chimneys; however, laboratory experiments showed that only females actively built and maintained chimneys, with some difference in the morphology of these structures between sexes. The social context had little influence on the construction of chimneys, which showed that the stimulus for constructing chimneys could be endogenous. Our results suggest that burrows with chimney of U. thayeri may have functions other than defense, and may act in regulating the internal conditions of the burrow, as observed in other crustaceans with such building behavior. http://zoolstud.sinica.edu.tw/Journals/51.5/598.pdf
Keywords: Construction behavior; Biogenic structure; Crab behavior